Research and implementation of motorcycle simulator controls - Josef Svoboda; Přemysl Toman; Adam Orlický (Acta Polytechnica CTU Proceedings, 2023)
The paper is focused on research in the field of motorcycle simulator controls from the rider’s point of view, with a focus on the longitudinal and lateral dynamics of vehicle. The subject of the research is the design and testing of a suitable composition of input signals controlled by the rider and their integration into the virtual scene. The design and testing of the communication interface between the HW simulator and the physical model of the motorcycle is mentioned in the paper as well. Furthermore, the work describes the suitable HMI elements of the motorcycle and their integration options into the simulator system. In conclusion of the article, various variants, and approaches for controlling the developed motorcycle simulator are discussed, including the possibilities of validating the achieved results.